2019
DOI: 10.3906/mat-1904-140
|View full text |Cite
|
Sign up to set email alerts
|

Null scrolls asB-scrolls in Lorentz–Minkowski 3-space

Abstract: Null scrolls, i.e. ruled surfaces whose base curve and rulings are both lightlike (null), are Lorentzian surfaces having no Euclidean counterparts. In this work we present reparametrization of nondegenerate null scroll as a Bscroll, i.e. as a ruled surface whose rulings correspond to the binormal vectors of a base curve. We prove that the curvature of a base curve, which determines the Gaussian and mean curvature of a null scroll, is invariant under such a reparametrization. We also determine a one-parameter f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In [11] it was shown that if the base curve of a null scroll is framed by a null frame L = (A, B, C) whose vector field B is collinear to the rulings of a null scroll, then the mean curvature H of a null scroll is given by H = k 3 , where k 3 is the curvature function of c with respect to L. Following this approach, in this paper we establish relations which will be used in defining null scrolls with a given base curve and prescribed curvatures. Results are presented in the next section.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…In [11] it was shown that if the base curve of a null scroll is framed by a null frame L = (A, B, C) whose vector field B is collinear to the rulings of a null scroll, then the mean curvature H of a null scroll is given by H = k 3 , where k 3 is the curvature function of c with respect to L. Following this approach, in this paper we establish relations which will be used in defining null scrolls with a given base curve and prescribed curvatures. Results are presented in the next section.…”
Section: Preliminariesmentioning
confidence: 99%
“…If we introduce another null frame for the base curve, related to the rulings of the null scroll, curvatures of the base curve are given by the following lemma. It is also known ( [11]) that the mean curvature H of S satisfies H(u) = k 3 (u), whereas for the Gaussian curvature K(u) = k 2 3 (u) holds. In order to obtain relation between the curvature of a base curve and the mean curvature of a null scroll, first we establish relations between vector fields of the frames L andL = (Ā(u),B(u),C(u)) = (c , e, c × e).…”
Section: Null Scrolls With Prescribed Curvaturesmentioning
confidence: 99%
See 1 more Smart Citation